An Integrated Buddhist Building Up the Immunity for the Development of Thai Youths’ Quality of Life through the Dare Project - Ruendee, Punya (Journal of Buddhist Innovation Review, 2024)
This dissertation entitled ‘An integrated Buddhist building up the immunity for the development of Thai youths’ quality of life through the Dare Project’ has three objectives: 1) to study the principles and processes in building up the immunity for the Development of Thai Youths’ quality of life through the Dare Project of Royal Thai Police, 2) to study Buddhist principles in building up the immunity for the Development of Thai Youths’ quality of life through the Dare Project, and 3) to propose the integrated Buddhist model in building up the immunity for the development of Thai youths’ quality of life through the Dare Project. This research employed the qualitative research methodology done by studying documents, related research works and in-depth interview of 23 scholars and then content analysis was made by means of the descriptive analysis accordingly. The research results clearly showed that building up the immunity is purposely assigned to solve the problem of drug done through strengthening the family, school, and community where all stakeholders are actively taken part in the prevention and solution of drug problem by the help of the Dare Project; students’ ability in solving personal problem especially drug problem is enragedly supported. As far as the Dare Project is concerned, it consists of the following: 1) planning to producing the Dare Police Teacher, 2) coordinating schools for joining the project, 3) educational institutions should be a part in making mechanism/networks of students, teachers, parents, polices and people in the community, 4) the regulations surrounding the educational institutions should be made by schools and Royal Thai police including involved departments. As for the Buddhist principles in building up the immunity for the Development of Thai Youths’ quality of life especially the ones in dealing with problem of drug are concerned, they are of five precepts, five virtues, Yonisomanasikãra, good friendship, six kinds of vices and six directions. The body of knowledge gained from the research showed that while conducting the Dare Project students are taught to understand the danger of drug, the solution based on the Dare Project, the application of Buddhist principles to bringing about the real happiness, the development of Thai youths’ quality of life, the model in building up the immunity for the development of Thai youths’ quality of life comes as ‘DSCB’ where D (D.A.R.E) the Dare Project, S means the dare school done through the project of moral development, C means community referring to Five Precepts Based Community where temple, community and school are actively taken part in, and B means Buddhist principles where Buddhist teachings are inserted in the topic of learning supported by the Dare Thinking through the given virtues correspondingly.